Pengaruh Edukasi Tentang Pernikahan Dini Terhadap Tingkat Pengetahuan Pada Remaja di SMA Negeri 1 Pinogaluman Kabupaten Bolaang Mongondow Utara - Miftahul Jannah Amala; Irne Wida Desiyanti; Atik Sunarmi (Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescence is a time when a person enters a new phase and is in the process of learning to distinguish between good and bad. Adolescents are expected to be able to prepare for the problems of life and their social environment. One of the many problems that occur in adolescents today is early marriage. Early marriage is caused by educational factors and lack of knowledge. The impact that can occur when performing early marriage is susceptible to uterine infections, cancer, and trauma, which is dangerous for mothers and babies. The purpose of this study was to determine the effect of education about early marriage on the level of knowledge of adolescents at SMA Negeri 1 Pinogaluman, North Bolaang Mongondow Regency. The method used is a type of quantitative research with a one-group pretest and posttest design approach and uses the Wilcoxon statistical test. From this study, the statistical test results obtained a p value of 0.000. This shows that the p value is <0.05, so Ha is accepted and H0 is rejected, so that it can be concluded that the education about early marriage on the level of knowledge in adolescents at SMA Negeri 1 Pinogaluman, North Bolaang Mongondow Regency, was affected. There where an increase in adolescent knowledge before and after being given education about early marriage.